Basaloid follicular hamartoma - Luana Amaral de Moura; Paulo Sergio Emerich Nogueira; Elton Almeida Lucas; Lucia Martins Diniz; Emilly Neves Souza (Sociedade Brasileira de Dermatologia (SBD), 2022)
Basaloid follicular hamartoma (BFH) is a rare and benign adnexal tumor that resembles basal cell carcinoma (BCC) and may present with different clinical manifestations. A mutation in the PTCH gene, involved in Gorlin-Goltz syndrome, could be associated with the pathogenesis of this neoplasm. We describe the case of a 7-year-old girl with multiple papules on her face.